Alimentary tract and pancreas. Stimulation of mucosal prostaglandin synthesis in human stomach and duodenum by antacid treatment. Issue 2 (February 1989) - Preclik, G; Stange, E F; Gerber, K; Fetzer, G; Horn, H; Ditschuneit, H
Abstract : The effect of a low dose antacid treatment on mucosal prostaglandin metabolism was studied in 15 healthy volunteers. A daily dose of 46 mmol (= 138 mval) Al(OH)3 and 42 mmol (= 84 mval) Mg(OH)2 with a titrated in vitro neutralising capacity of 272 mval of H+ was given for three weeks. Total prostaglandin formation and the prostaglandin profile as well as the degradation of PGE2 were assayed by incubating homogenates of endoscopic biopsies from antral and duodenal mucosa with the precursor (14C)arachidonic acid. Total prostaglandin synthesis in antrum (623 (110) pmol/mg protein) and duodenum (432 (72) pmol/mg) was stimulated after three weeks administration of low dose antacids by 176% (p less than 0.05) and 154% (p less than 0.05), respectively. An untreated control group exhibited no significant changes. In contrast, the prostaglandin profile showed only a small increase of the prostacyclin metabolite 6-keto PGF1a (p less than 0.05) at the expense PGD2. PGE2 catabolism was unaffected. This enhanced activity of mucosal prostaglandin cyclooxygenase might represent one possible mechanism of action of a low dose antacid treatment.